Genetic variants of tumor necrosis factor-α and its levels: A correlation with dyslipidemia and type 2 diabetes susceptibility. Issue 3 (June 2019) - Patel, Roma; Palit, Sayantani Pramanik; Rathwa, Nirali; Ramachandran, A.V.; Begum, Rasheedunnisa
Summary: Background & aim: Tumor necrosis factor-α (TNF-α) and its genetic variants are implicated in the development of type 2 diabetes (T2D) as a result of systemic inflammation, dyslipidemia, and insulin resistance. The aim of the present study was to investigate i) single nucleotide polymorphisms (SNPs) of TNF-α and its association with altered TNF-α transcript levels and plasma concentrations ii) free fatty acid (FFA) concentrations as a marker for dyslipidemia and its association with TNF-α and iii) genotype–phenotype correlation analysis in T2D patients. Methods: Plasma and PBMCs were separated from venous blood of 478 diabetic patients and 502 age-matched non-diabetic individuals. Genomic DNA was isolated from PBMCs and RNA was isolated from PBMCs and adipose tissue samples. PCR-RFLP was used for genotyping and qPCR to estimate TNF-α levels. TNF-α and FFA concentrations were estimated from plasma samples by ELISA. Results: Our study suggests: i) involvement of TNF-α  −857 C/T in T2D patients ( p  < 0.0001), ii) 2.072 and 6.7 fold elevation in TNF-α transcript levels in patients' PBMCs and adipose tissues respectively, increased plasma TNF-α ( p  = 0.0122) particularly in obese patients ( p  = 0.0405), increased plasma FFA ( p  = 0.0215) and, iii) association of TNF-α  −238 G/A with body mass index (BMI) ( p  = 0.0270) and,  −857 C/T with fasting blood glucose (FBG) ( p  = 0.0122) and triglycerides (TG) ( p  = 0.0015). Correlation analysis suggests that TNF-α concentrations are positively correlated with BMI ( r  = 0.3, p  = 0.04) and negatively correlated with HDL ( r  = −0.39, p  = 0.001) while the FFA concentrations are positively correlated with BMI ( r  = 0.35, p  = 0.0004). Conclusion: It can be concluded that the genetic variant of TNF-α along with elevated TNF-α and FFA concentrations play a role in the development of dyslipidemia which could be a potent risk factor towards T2D in Gujarat population.